A method of evaluating safety Of construction Of infrastructure. - Noorzaei, Jamaloddin; Jaafar, Mohd Saleh; Mohammad, Thamer Ahmad; Abdulrazeg, Aeid. A.; Khanehzaei, Parviz (2010)

(untitled)
A method of safety evaluation of roller compacted concrete dam during construction and operation phase wherein the RCC dam is constructible through a plurality of construction stages is provided, the method includes the steps of simulating a sequence of the plurality of construction stages, performing thermal analysis of the plurality of construction stages, performing structural analysis on the plurality of construction stages, performing crack prediction of the plurality of construction stages and recommending a safe sequence of the plurality of construction stages in addition to assessing the response of RCC dam during lifetime.